Remarks on (Purported) Translators' Tasks and Translation Teaching - Antunović, Goranka (Array, 2003)
Translator training requires contribution by experts in a variety of fields. The article singles out language experts, who sometimes fail to realize that the linguistic behavior of translators need not necessarily follow the same principles as that of a different group of language professionals. Several examples are given of recommendations that could be heard at recent translator seminars in Zagreb that are not in tune with the prevalent contemporary understanding of translation process and translators’ role. They involve insistence on a single pattern as ‘ the right one’ and thereby ignore both the textual and the non-linguistic determinants of translation activity. The author favors a different understanding of translators’ tasks and desired linguistic behavior, namely the one asserting translation as an intentional communicative process. The position implies that the translator should take note of and act in line with characteristics of the situational (including textual) context and the communicative intentions and expectations of the source and target participants in the translation process.